الإضراب والهوية النقابية - منسول، الصالح (جامعة محمد خيضر بسكرة - كلية العلوم الإنسانية والاجتماعية - مخبر المسألة التربوية في ظل التحديات الراهنة, 2023)
لقد شكل فعل الإضراب في منحاه الاجتماعي دلالة لرسم الهوية النقابية للنقابات المستقلة في الجزائر، فتزايد هذا الفعل ممارسة في أشكال المتعددة يعبر عن ذلك الاحتقان الاجتماعي الذي تعاني منه الفئات العمالية داخل عالم الشغل، فالمنحى الجديد للحركات الاجتماعية خاصة النقابات منها أصبحت تمارس فعل الإضراب في شكله الأداتي والمتجذر بغية رسم مسارها النقابي وتحقيق مطالبها المشرع قانونا ومن جهة أخرى لتفعيل هويتها النقابية التي تنعكس في ممارسة الحق النقابي دون تضييق بالإضافة إلى المشاركة في اتخاذ القرارات ضمن استراتيجياتها ومشروعها النقابي، فضمن هذا المقال سنركز على تحليل دور الإضراب كفعل اجتماعي في رسم معالم الهوية النقابية للنقابات المستقلة في الجزائر. The act of striking in its social aspect was an indication of the trade union identity of the independent trade unions in Algeria. The increasing practice of this act in multiple forms reflects the social congestion experienced by groups in the world of employment, the new grants to social movements, especially trade unions, have become active. Strikes in the form of instruments and worthwhile in order to chart its trade union course and fulfil its legally legitimate demands. On the other hand, to activate its trade union identity, which is reflected in the exercise of the trade union right without restriction in addition to Participation in decision-making within its strategies and trade union projects. In addition to this article, we will focus on analysis The role of the strike as a social act in shaping the trade union identity of independent trade unions in Algeria.
Keywords: الإضراب الوظيفي -- الحركات الاجتماعية -- الهوية النقابية -- النقابات الجزائرية